2018
DOI: 10.1111/ijcs.12464
|View full text |Cite
|
Sign up to set email alerts
|

Global personal spirituality: Concept, measurement, and correlates across cultures

Abstract: The present study introduces a scale measuring a universal trait Global Personal Spirituality (GPS), which is independent of a person’s religion or religious belief. A series of confirmatory factor analyses with progressively more restrictive constraints were carried out to assess the GPS scale’s measurement invariance using subjects who were 30 to 69 years of age, and were from China (N = 453), Japan (N = 314), Korea (N = 350), and the United States (N = 436). The study also examines correlates of the GPS sca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…Significant differences have been observed in spirituality between men and women. Females tend to participate more than males in spiritual activities (Ansari, 2016; Mathur et al , 2018). It is expected that because of their stronger inclination toward spiritualism, females might tend to experience higher psychological capital, thereby leading to better QWL as compared to males.…”
Section: Introductionmentioning
confidence: 99%
“…Significant differences have been observed in spirituality between men and women. Females tend to participate more than males in spiritual activities (Ansari, 2016; Mathur et al , 2018). It is expected that because of their stronger inclination toward spiritualism, females might tend to experience higher psychological capital, thereby leading to better QWL as compared to males.…”
Section: Introductionmentioning
confidence: 99%
“…Personal spirituality could be linked with self-compassion, a construct that entails self-kindness, common humanity and mindfulness (Neff, 2010) and the same lowers conspicuous consumption among consumers. Engaging in personal spirituality also results in individuals finding more meaning and purpose in their purchases (Baldacchino, 2017;Mathur et al, 2018;Lee et al, 2016;Prieto and J odar, 2020). It has been demonstrated that spirituality affects consumer behavior (Ulvoas-Moal, 2011; Lee et al, 2016;Mathur et al, 2018).…”
Section: Global Personal Spirituality (Gps)mentioning
confidence: 99%
“…Engaging in personal spirituality also results in individuals finding more meaning and purpose in their purchases (Baldacchino, 2017;Mathur et al, 2018;Lee et al, 2016;Prieto and J odar, 2020). It has been demonstrated that spirituality affects consumer behavior (Ulvoas-Moal, 2011; Lee et al, 2016;Mathur et al, 2018). Personal spirituality and consumer decisions regarding luxury fashion goods and counterfeits have been found to have a negative link (Khatoon and Rehman, 2021).…”
Section: Global Personal Spirituality (Gps)mentioning
confidence: 99%
See 1 more Smart Citation
“…Lives are experienced as meaningful when they make sense, are purposeful and significant beyond the ordinary (George & Park, 2016; Martela & Steger, 2016). Research on the sources of meaning in life has consistently recognized social connections, religion and spirituality as robust sources of meaning (King et al, 2016; King & Hicks, 2021; Mathur et al, 2018); however, the role of consumption has been less frequently acknowledged. Many philosophers, faith leaders and sociologists consider consumption antithetical to a meaningful life (Izberk‐Bilgin, 2010; Kashdan & Breen, 2007; Kilbourne, 1987; Rudmin & Kilbourne, 1996).…”
Section: Introductionmentioning
confidence: 99%